Perancangan Mebel Multifungsi Untuk Home Office - Constantine, Yuvensius Kevin (Intra, 2015)
The convenience of mobility and the efficiency of work are greatly needed nowadays, thus, a lot ofÂ  companies are now starting from a home office. The work activities, along with another activities when people are not working have become a requirement to be fulfilled and obtained from a furniture. Generally, workstation furnitures only meet the work activities alone, meanwhile, the other activities arenât being fulfilled. Therefore, a multi-functional furniture is needed in order to accommodate the working activities and another things as well. Forms and colors of the furniture must use universal colors in order to be one with the room related. Ergonomy and material standards are also influential in order to support the user working activities.